Sex-disaggregated population analysis in patients with hidradenitis suppurativa - Sabat, Robert; Tsaousi, Athanasia; Ghoreschi, Kamran; Wolk, Kerstin; Schneider-Burrus, Sylke (Frontiers in Medicine, 2022)
Background Hidradenitis suppurativa (HS) is a common chronic inflammatory skin disease, which affects both sexes. Objectives Identification of sex-specific risk factors, comorbidity, clinical manifestations, and treatments in HS patients. Methods A non-interventional, cross-sectional, mono-centric study with 500 HS patients. All patients were examined by dermatologists. Prospectively collected demographic, anamnestic, clinical data, and blood parameters were evaluated. Results There were no significant differences in age at HS onset and in disease duration between female and male patients. Furthermore, no differences regarding the family history for HS were found between sexes. Regarding further risk factors for HS, central obesity was more frequent in women while extensive cigarette smoking and acne vulgaris were more commonly found among male patients. Regarding comorbidity, lower HDL-levels were significantly more frequent in men. Female patients were found to suffer significantly more often from back pain, especially in the neck/shoulder region and lower back. Analyzing the clinical manifestation of HS, the groin was more frequently involved in women and the axillae in men. Women showed a higher number of skin sites with inflammatory nodules, whereas fistulas were observed more frequently in men. Nevertheless, there was no difference in HS treatment applied to female vs. male patients. Limitations Data were obtained from a mono-centric study. Conclusion Significant differences in HS risk factors, comorbidity, and clinical manifestation exist between female and male patients. Thus, sex-specific differences should be taken into account in the prevention as well as medical and surgical treatment of HS patients.